2010
DOI: 10.1016/j.wasman.2009.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five organic wastes regarding their behaviour during composting: Part 2, nitrogen dynamic

Abstract: Author-produced version of the article published in Waste Management Original publication available at www.elsevier. com -doi:10.1016/j.wasman.2009.10.018 2 Abstract 1 This paper aimed to compare household waste, separated pig solids, food waste, pig slaughterhouse sludge 2 and green algae regarding processes ruling nitrogen dynamic during composting. For each waste, three 3 composting simulations were performed in parallel in three similar reactors (300L), each one under a constant 4 aeration rate. The aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 17 publications
3
43
0
1
Order By: Relevance
“…Composting is a biological process in which organic matter (OM) can be utilized by aerobic thermophilic and mesophilic microorganisms as substrate and mainly converted into mineralized products (CO 2 , H 2 O, NH 4 + ) or stabilized OM (mostly as humic substances) (Bernal et al, 2009;He et al, 2009;de Guardia et al, 2010a;de Guardia et al, 2010b). Although composting has been widely practiced with its final products being used as fertilizer or soil amendment, there are still knowledge gaps in understanding it due to the high variety and heterogeneity of feedstocks (Li et al, 2008;Himanen and Hänninen, 2011).…”
Section: China Pollution Source Census Issued By the Ministry Of Envimentioning
confidence: 99%
“…Composting is a biological process in which organic matter (OM) can be utilized by aerobic thermophilic and mesophilic microorganisms as substrate and mainly converted into mineralized products (CO 2 , H 2 O, NH 4 + ) or stabilized OM (mostly as humic substances) (Bernal et al, 2009;He et al, 2009;de Guardia et al, 2010a;de Guardia et al, 2010b). Although composting has been widely practiced with its final products being used as fertilizer or soil amendment, there are still knowledge gaps in understanding it due to the high variety and heterogeneity of feedstocks (Li et al, 2008;Himanen and Hänninen, 2011).…”
Section: China Pollution Source Census Issued By the Ministry Of Envimentioning
confidence: 99%
“…De otro lado, la pérdida de nitrógeno en el proceso, principalmente en forma de amoniaco, es uno de los temas más abordados en las investigaciones debido a su relación con la calidad del producto y a las emisiones de NOx que se relacionan con los GEI [65]. Como alternativa para mejorar la calidad del producto final, los ensayos de escala de laboratorio pueden indicar si las opciones que se pretendan evaluar pueden ofrecer resultados satisfactorios en términos de biodegradabilidad o si por el contrario podrían afectar el proceso.…”
Section: Análisis De Las Tendencias De Investigación Más Estudiadas Eunclassified
“…This disagrees with the results of De Guardia et al (2008), Körner and Stegmann (2003) and Liang et al (2004) who found higher ammonia emissions with higher aeration rates. This difference could result from the reaction of the different nitrifying bacteria with aeration and the nature of the compost material (De Guardia et al, 2009). The results of this study therefore suggest that both frequencies of turning could be used with little effects on the properties of the finished compost.…”
Section: Nutrient Content Of the Prepared Manuresmentioning
confidence: 99%